PHYSICAL EDUCATION AND VOCATIONAL TRAINING (Fiep Bulletin - online, 2011)
This study presents a problem addressed in educational literature, but of great significance since ancient times, as is well known maxim "Men sana in corpore sano", which indicates the close link that exists between the intellectual and physical personality development. On investigation it conducts an analysis of trends in Physical Education, specifically addressing the historical aspect of their integration into the educational process, noting their educational potential. Address the essential concepts of this study (physical education, professional profile and training), their definitions and mutual relations. Still, he recalls his presence and relationship to other areas of human development such as sport, health, culture, tourism and peace.